New data on the genus Cheilosia Meigen (Diptera, Syrphidae) from Central Asia, with descriptions of two new species and a key to the ‘group C’ - Barkalov, Anatolij V. (Zootaxa, 2020)
New information is given on the distribution of Cheilosia Meigen species (Diptera, Syrphidae) in Central Asia, together with a description of two new species. The new species, Cheilosia teneripilosa sp. nov. and Cheilosia vadimi sp. nov., belong to the subgenus Montanocheila Barkalov. Cheilosia teneripilosa differs from its close allies by a set of the following characters: eyes with long black hairs, legs of male completely black, abdomen predominantly with light hairs, superior lobe of hypandrium with a very small left process. Cheilosia vadimi is close to C. kirgizorum Peck, but differs by shorter hairs on the eyes and scutum, and a completely different shape of the superior lobe of the hypandrium. A revised key is given to the ‘group C’ species of Cheilosia from Central Asia (those with haired eyes, bare face and absence of strong bristles on scutellar hind margin). The descriptions of the new species are accompanied by drawings of the head and male genitalia.